Influence of Physicollydrological Characteristics of Soils on Paddy Cultivation - Yadav, R.C.; Bhola, S.N. (Journal of Soil and Water Conservation, 2022)
Laterite soils are known as major paddy supporting soils. These soils associated with humid climate make Midnapur district of West Bengal, one of the highest paddy producing district of the country. Soils being a significant common dominator in all the systems such as irrigation, drainage or rainfall runoff relationship, their moisture characteristics are basic to any above consideration. The premises that major zone of agronomic and hydrologic activity lies above some depth has been accepted by Holtan et al (1967) in hydrologic grouping of soils. Rooting is reported to be often restricted in lateritic highly weathered tropical subsoil, which are generally high in oxides of iron and alluminium (Humbert 1973). The soils of the Midnapur district also exhibit condition of poor drainage when wet and limit the growth of most of the crops but at the same time favour the paddy crop. For meeting the requirements of the farmers growing different crops in general and paddy crop in particular, there is a need for understanding water management system in accordance with physico-hydrologic characteristics of soils.